(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zulkarnaini, Sujianto, Wawan. 2022. Short Communication: Sustainability of ecological dimension in peatland management in The Giam Siak Kecil Bukit Batu Landscape, Riau, Indonesia. Biodiversitas 23: 1822-1827. The Giam Siak Kecil-Bukit Batu (GSKBB) in Riau Province, Indonesia, is assigned as a biosphere reserve due to its importance in terms of biodiversity conservation and ecosystem services provision, particularly due to the existence of large tracts of peat swamp forest. However, GSKBB landscape is threatened by various anthropogenic activities of using peatland resources because such activities are often carried out in an exploitative and destructive manner. This study aims to analyze the sustainability of the ecological dimension in peatland management in the GSKBB landscape. Methodologically, the design of this research used a mixed approach by combining quantitative and qualitative methods to determine the sustainability of peatland management. Primary data was collected through field observations and in-depth interviews with key informants from the GSKBB Biosphere Reserve management board, local government, private companies, non-governmental organizations (NGOs), and other local stakeholders. Computer programming RAPPEAT was used to analyze the sustainability index. The results of sustainability analysis of the ecological dimension of peatland management in the GSKBB landscape obtained a sustainability index of 46.5% or classified as less sustainable (<50). This value suggests that the condition of the peatland ecosystem is under pressure viewed from the ecological aspect. This is reinforced by the results of field observations which showed that the peatland ecosystem is experiencing damage and quality degradation such as land degradation, illegal logging, and land conversion. Leverage analysis obtained two attributes that are sensitive to the sustainability index of ecological dimension, namely land use (RMS = 3.84) and land conversion (RMS = 3.11). These two attributes indicate that the condition of the peatland ecosystem is strongly influenced by plantation activities in the area.